Cleaning of fouled membranes using enzymes from a sulphidogenic bioreactor - Melamane, Xolisa L (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2004)
Maintenance of membrane performance requires inevitable cleaning or defouling of fouled membranes. Membrane cleaning using enzymes such as proteases, lipases, Î±-glucosidases from a sulphidogenic bioreactor was investigated. At first, dilute and concentrated enzyme extract were prepared form the sulphidogenic pellet. Enzyme assays on 0.5 % azocaisen, 1 % triacetin and 1 mg/ml Ï -nitrophenyl-Î±-D-glucopyranoside were performed using the concentrated enzyme extract (0 "“ 200 mg/ml). For membrane fouling, an abattoir effluent was obtained from Ostritech Pty (Ltd), Grahamstown, South Africa. The effluent was characterised for presence of potential foulants such as lipids, proteins, amino acids and carbohydrates. Static fouling of polysulphone membranes (0.22 Î¼m, 47 mm) was then performed using the abattoir effluent. Cleaning of the fouled membranes was also performed using at first the dilute and then the concentrated form (200 mg/ml) of enzyme extracts. Qualitative and quantitative biochemical analysis for proteins, lipids and carbohydrates was performed to ascertain the presence of foulants on polysulphone membranes and their removal by dilute or concentrated enzyme extracts. The ability of dilute enzyme extracts to remove proteins lipids, and carbohydrates fouling capillary UF membrane module; their ability to restore permeate fluxes and transmembrane pressure after cleaning/defouling was also investigated. Permeate volumes from this UF membrane module were analysed for protein, amino acids, lipids, and carbohydrates concentrations after fouling and defouling. Fouling was further characterized by standard blocking, cake filtration and pore blocking models using stirred UF cell and polyethersulphone membranes with MWCO of 30 000, 100 000 and 300 000. After characterization of fouling, polyethersulphone membranes with MWCO of 30 000 and 300 000 were defouled using the concentrated enzyme extract (100 mg ml). Enzyme activities at 200 mg/ml of enzyme concentration were 8.071 IU, 86.71 IU and 789.02 IU for proteases, lipases and Î±-glucosidases. The abattoir effluent contained 553 Î¼g/ml of lipid, 301 Î¼g/ml of protein, 141 Î¼g/ml of total carbohydrate, and 0.63 Î¼g/ml of total reducing sugars. Proteins, lipids and carbohydrates fouling polysulphone membranes after a day were removed by 23.4 %, when a dilute enzyme was used. A concentrated enzyme extract of 200 mg/ml was able to remove proteins, lipids and carbohydrates up to 5 days of fouling by 100 %, 82 %, 71 %, 68 % and 76 % respectively. Defouling of dynamically fouled capillary ultrafiltration membranes using sulphidogenic proteases was successful at pH 10, 37Â°C, within 1 hour. Sulphidogenic proteases activity was 2.1 U/ml and flux Recovery (FR %) was 64. Characterization of fouling revealed that proteins and lipids were major foulants while low concentration of carbohydrates fouled polyethersulphone membranes. Fouling followed standard blocking for 10 minutes in all the membranes; afterwards fouling adopted cake filtration model for membranes with 30 000 MWCO and pore blocking model for membranes with 300 000 MWCO. A concentration of 100 mg/ml of enzyme extract was able to remove fouling from membranes with MWCO of 30 000. Defouling membranes that followed pore blocking model i.e. 300 000 MWCO was not successful due to a mass transfer problem. From the results of defouling of 30 000 and 300 000 MWCO it was concluded that defouling of cake layer fouling (30 000 MWCO) was successful while defouling of pore blocking fouling was unsuccessful due to a mass transfer problem. The ratio of enzymes present in the enzyme extract when calculated based on enzymatic activity for proteases, lipases and Î±-glucosidases was 1.1 %, 11 % and 87.9 %. It was hypothesized that apart from proteases, lipases, Î± and Î²-glucosidases; phosphatases, sulphatases, amonipeptidases etc. from a sulphidogenic bioreactor clean or defoul cake layer fouling by organic foulants and pore blocking fouling provided the mass transfer problem is solved. However, concentration of enzymes from a sulphidogenic bioreactor has not been optimized yet. Other methods of concentrating the enzyme extract can be investigated for example use of organic solvents.
Keywords: Membrane filters; Membrane filters -- Fouling; Enzymes -- Biotechnology; Enzymes -- Purification; Water -- Purification -- Membrane filtration; Ultrafiltration